Numerical analyses of stability of a gradually raised tailings dam - Zardari, Muhammad Auchar (Luleå tekniska universitet, Geoteknologi, 2013)
Numerical analyses are presented in this thesis to address potential stability problems that may occur during gradual raisings and under seismic loading conditions of Aitik tailings dam in northern Sweden. The dam is mainly raised using upstream construction method. It is planned to raise the dam gradually in several stages. Two dam parts were studied. The first dam part is a straight dam portion, and the second dam part is a corner. The main concerns associated with future raisings of the straight dam part were: (i) the stability of the dam could be affected by an increase in excess pore pressures during sequential raisings, (ii) how to gradually strengthen the dam by using rockfill berms as supports in such a way that required slope stability can be achieved with a minimum volume of rockfill berms, and (iii) if the dam is subjected to seismic loading, whether or not an increase in excess pore pressures could lead to extensive liquefaction which may cause a failure. The problems related to the dam corner were that tension zones and/or low compression zones could develop because of the horizontal pressure of the stored tailings on the inside of the curvature of the dam corner.Numerical analyses were conducted on both the dam parts using finite element method. Two dimensional (2D) plane strain finite element model was utilized to analyse the straight dam. The dam corner was analysed with both the three dimensional (3D) finite element model, and the 2D axisymmetric finite element model. Coupled deformation and consolidation analyses, and slope stability analyses were performed on both the dam parts to simulate gradual raisings, and to compute safety factors. In addition to this, dynamic analyses were carried out on the straight dam part to evaluate the potential for liquefaction, and seismic stability of the dam. The seismic behaviour of the dam was analysed for two cases: (i) a normal case (earthquake of 3.6 Swedish local magnitude), and (ii) an extreme case (earthquake of 5.8 moment magnitude).The results of the ...